2014
DOI: 10.1097/aln.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane-induced Apoptosis of Neurons and Oligodendrocytes in the Fetal Rhesus Macaque Brain

Abstract: Background The authors have previously shown that exposure of the neonatal nonhuman primate (NHP) brain to isoflurane for 5 h causes widespread acute apoptotic degeneration of neurons and oligodendrocyte. The current study explored the potential apoptogenic action of isoflurane in the fetal NHP brain. Methods Fetal rhesus macaques at gestational age of 120 days (G120) were exposed in utero for 5 h to isoflurane anesthesia (n = 5) or to no anesthesia (control condition; n = 4), and all regions of the brain we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 40 publications
(84 reference statements)
6
167
2
3
Order By: Relevance
“…Common general anesthetics such as ketamine and isoflurane have been reported to induce neuroapoptosis and cellular degeneration in actively developing brains in rodents (Hayashi et al, 2002;Ikonomidou et al, 1999;Jevtovic-Todorovic et al, 2003;Ma et al, 2007;Sanders et al, 2009Sanders et al, , 2010Scallet et al, 2004) and nonhuman primates (Creeley et al, 2013;Brambrink et al, 2012Brambrink et al, , 2010Slikker et al, 2007;Zou et al, 2009). Dexmedetomidine is a sedative and anesthetic with a different mechanism of action than ketamine and isoflurane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common general anesthetics such as ketamine and isoflurane have been reported to induce neuroapoptosis and cellular degeneration in actively developing brains in rodents (Hayashi et al, 2002;Ikonomidou et al, 1999;Jevtovic-Todorovic et al, 2003;Ma et al, 2007;Sanders et al, 2009Sanders et al, , 2010Scallet et al, 2004) and nonhuman primates (Creeley et al, 2013;Brambrink et al, 2012Brambrink et al, , 2010Slikker et al, 2007;Zou et al, 2009). Dexmedetomidine is a sedative and anesthetic with a different mechanism of action than ketamine and isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that certain common anesthetic agents, such as ketamine and isofluorane, cause widespread apoptosis and neurodegeneration in neonatal rat (Hayashi et al, 2002;Ikonomidou et al, 1999;Jevtovic-Todorovic et al, 2003;Ma et al, 2007;Sanders et al, 2009Sanders et al, , 2010Scallet et al, 2004) and monkey (Creeley et al, 2013;Brambrink et al, 2012Brambrink et al, , 2010Slikker et al, 2007;Zou et al, 2009) brains. While ketamine and isoflurane have different pharmacologic actions in exerting their respective anesthetic effects (Brambrink et al, 2010;Haberny et al, 2002;Ma et al, 2007;Mellon et al, 2007), they both induce similar types of neuroapoptotic lesions and in similar locations in developing brains (Brambrink et al, 2010;Slikker et al, 2007;Zou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Brains of both fetal [24] and neonatal rhesus macaques [8,11] display signs of neuronal apoptosis upon exposure to isoflurane (0.7 -1.5 Vol.% for 5 hours). In humans, there is epidemiological evidence to suggest a modestly elevated risk of adverse behavioural or developmental outcomes in children who were exposed to anaesthesia during early childhood [1,3,4].…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to isoflurane, which affects various cell types outside and inside the brain [8,24], causes a panoply of cardiorespiratory and metabolic side effects [10]. Its use in newborn rodents is associated with considerable mortality [25].…”
Section: Introductionmentioning
confidence: 99%
“…Se sabe que el desarrollo neurológico en animales se ve alterado con la administración de anestésicos generales aún por periodos cortos. Estudios preclínicos en fetos de roedores, cerdos y monos han mostrado que la exposición a anestésicos inhalatorios y drogas sedantes causa apoptosis neuronal 23,24 , exposición que también ha demostrado asociarse con trastornos del aprendizaje 25 . Este tema largamente debatido y que ha sido motivo de varias editoriales en revistas anestesiológicas 26,27,28 permanece aún siendo controversial.…”
Section: Técnica Anestésica Y Fetounclassified